Acetabular Revision Arthroplasty Based on 3-Dimensional Reconstruction Technology Using Jumbo Cups - Shen, Xianyue; Tian, Hao; Li, Yang; Zuo, Jianlin; Gao, Zhongli; Xiao, Jianlin (Frontiers in Bioengineering and Biotechnology, 2022)
Background This study was aimed at evaluating the changes in cup coverage (CC) and hip center of rotation (HCOR) in acetabular defects of various severities treated with acetabular revision using jumbo cups. Methods A total of 71 hips were included. The American Academy of Orthopedic Surgeons (AAOS) classification of these patients was as follows: 9 patients, AAOS I; 11 patients, AAOS II; and 13 patients, AAOS III. A three-dimensional (3D) implant simulation technique was used to visualize the placement of jumbo cups during revision arthroplasty. The acetabular anteversion, inclination, CC, and the HCOR were measured. Results The inclination and anteversion of simulated acetabular cups in AAOS I–Ⅲ groups were consistent with the normal acetabular anatomy. Compared with the controls, in AAOS I–Ⅲ groups, the HCOR was significantly increased and CC was significantly decreased. The HCOR elevation was significantly higher in AAOS Ⅲ patients than in AAOS I (P = 0.001) and AAOS Ⅱ patients (P < 0.001). The use of the jumbo cup technology for acetabular revision would decrease the CC in AAOS I–Ⅲ patients to 86.73%, 82.07%, and 76.29%, respectively. Conclusion Our study demonstrated that in patients with acetabular defects, acetabular revision arthroplasty using jumbo cups will lead to decreased CC and HCOR upshift. Upon classifying these patients according to the AAOS classification, CC decreased with the severity of acetabular defects, and the elevation of the HCOR in AAOS Ⅲ patients exceeded 10 mm and was significantly higher than in other patients.